The news consumption of digital natives - Valkama, Suvi (2015)
Digitalization has shaped the newspaper market and nowadays the news consumption of people increasingly takes place in the online environment. At the same time when print newspapers can no longer be considered as the revenue drivers for media companies, especially digital natives remain reluctant to pay for news content in the digital media. As a result, the digitalization brought by the Internet is challenging the operations of media companies and they need to find new ways to attract consumers to using their services.